Green building technology delay factor in Malaysia construction industry - Muhammad, Nik Wan; Musa, Suria (Universiti Utara Malaysia, 2020)
This research is for identify the primary causes effect of delay in green building constructions project in Malaysia with study several article who are related with delay factor in green building constructions. This research involved several countries related. There are two objectives to this study they are to investigate and identify the delay factor in green building development in Malaysia and to investigate the trend of green building in Malaysia construction industry. The result was come from systematic method or study case. It shows in 20 articles related with green building. The analysis of the data then provided three frameworks or subject for delay factors. They are Cost to implement the green building in project, lack of knowledge and information and people. These three subjects have different variable related with it and every once framework is clarified and explain in detail. These three frameworks also merged and added in the literature review. Again, the different components related is discussed in detail.